Chronically endurance‐trained individuals preserve skeletal muscle mitochondrial gene expression with age but differences within age groups remain. Issue 12 (18th December 2014) - Johnson, Matthew L.; Lanza, Ian R.; Short, Daniel K.; Asmann, Yan W.; Nair, K. Sreekumaran
Abstract Maintenance of musculoskeletal function in older adults is critically important for preserving cardiorespiratory function and health span. Aerobic endurance training (ET) improves skeletal muscle metabolic function including age‐related declines in muscle mitochondrial function. To further understand the underlying mechanism of enhanced muscle function with ET, we profiled the gene transcription (mRNA levels) patterns by gene array and determined the canonical pathways associated with skeletal muscle aging in a cross‐sectional study involving vastus lateralis muscle biopsy samples of four subgroups (young and old, trained, and untrained). We first analyzed the sedentary individuals and then sought to identify the pathways impacted by long‐term ET (>4 years) and determined the age effect. We found that skeletal muscle aging in older sedentary adults decreased mitochondrial genes and pathways involved in oxidative phosphorylation while elevating pathways in redox homeostasis. In older adults compared to their younger counterparts who chronically perform ET however, those differences were absent. ET did, however, impact nearly twice as many genes in younger compared to older participants including downregulation of gene transcripts involved in protein ubiquitination and the ERK/MAPK pathways. This study demonstrates that in individuals who are chronically endurance trained, the transcriptional profile is normalized for mitochondrial genes but aging impacts the number of genes that respond to ET including many involved in protein homeostasis and cellular stress.